1987
DOI: 10.1002/yea.320030208
|View full text |Cite
|
Sign up to set email alerts
|

Nucleotide phosphotransferase, nucleotide kinase and inorganic pyrophosphatase activities of killer virions of yeast

Abstract: The intracellular killer virions of yeast co-purify with an RNA polymerase activity which catalyzes the synthesis of full-length transcripts of the two viral genomic double-stranded RNA segments. This polymerase utilizes ribonucleoside diphosphates or triphosphates as substrates. The virions have other associated nucleotide-metabolizing enzyme activities, including nucleoside diphosphate kinase, adenosine monophosphate kinase, and nucleoside triphosphate phosphotransferase, an activity which catalyzes the exch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

1989
1989
2016
2016

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 31 publications
0
6
0
Order By: Relevance
“…It is thus conceivable that the GDP produced in this process was incorporated at the 5Ј-end of the viral RNA during transcription initiation. Georgopoulos et al (36) has observed that L-A virions are associated with numerous nucleotide-metabolizing enzyme activities, including nucleoside triphosphate phosphotransferase, nucleoside diphosphate and monophosphate kinases, in addition to inorganic pyrophosphatase activity, and speculated that these enzymes may allow the virus to utilize nucleotide pools distinct from those used in host cell transcription. However, the results shown in this work raise the possibility that some of the enzymatic activities associated with the virion are directly involved in the metabolism of phosphate group at the 5Ј termini of viral transcripts.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It is thus conceivable that the GDP produced in this process was incorporated at the 5Ј-end of the viral RNA during transcription initiation. Georgopoulos et al (36) has observed that L-A virions are associated with numerous nucleotide-metabolizing enzyme activities, including nucleoside triphosphate phosphotransferase, nucleoside diphosphate and monophosphate kinases, in addition to inorganic pyrophosphatase activity, and speculated that these enzymes may allow the virus to utilize nucleotide pools distinct from those used in host cell transcription. However, the results shown in this work raise the possibility that some of the enzymatic activities associated with the virion are directly involved in the metabolism of phosphate group at the 5Ј termini of viral transcripts.…”
Section: Discussionmentioning
confidence: 99%
“…1S, A and B). A potent inorganic pyrophosphatase activity has been observed to be associated with L-A virions (36). It is likely that the enhanced release of P i was not caused by nucleoside triphosphatase activity per se but by hydrolysis of inorganic pyrophosphate generated as a byproduct from polymerization of the 6-nt transcript (5Ј-GAAAAA).…”
Section: Volume 285 • Number 30 • July 23 2010mentioning
confidence: 99%
See 1 more Smart Citation
“…The bold regions are the two 11-base repeats that fall in the loops of the predicted stem-loop structures. [Adapted from Huan et al (19911.1 Ghabrial and Havens, 19891, a replicase Nemeroff and Bruenn, 19861, a protein kinase (Ghabrial and Havens, 19921, a nucleotide phosphohydrolase (Dowhanick et al, 19941, a nucleotide phosphotransferase, a nucleotide kinase, and an inorganic pyrophosphatase (Georgopoulos and Leibowitz, 1987). Furthermore, the pol domain of the 170-kDa CP-RDRP fusion protein of the yeast L-A virus has a n ssRNA binding activity (Fujimura and Wickner, 1988a).…”
Section: F Functional Domains In Proteins Of Totiuirusesmentioning
confidence: 99%
“…The latter two appear to have incorporated one and two C residues respectively. Because L‐A virions are associated with nucleoside mono‐ and diphosphate kinase activities (Georgopoulos and Leibowitz, ), empty particles may incorporate a couple of Cs if CMP is generated by minor degradation of the template RNA during incubation. 11‐ and 14‐mers were isolated from the gel, digested with S1 nuclease, and analyzed on TLC.…”
Section: Resultsmentioning
confidence: 99%